Evaluation of Physical Therapy Effectiveness after Anterior Cruciate Ligament Reconstruction (Baltic Journal of Sport and Health Sciences, 2012)
Research background and hypothesis. The aim of physical therapy after sports trauma is to help patients to restore physical activity as it was before injury. The participants who applied for intensive physical therapy after anterior cruciate ligament reconstructive surgery will achieve better leg muscle strength results.Research aim was to compare the effectiveness of intensive and traditional rehabilitation of the knee extensor and flexor muscle strength after the surgery for patients after anterior cruciate ligament reconstruction.Research methods. The method that we used was “Biodex Medical System 3 PRO” for the knee muscle strength. A total of 30 patients were enrolled in this study. The subjects were divided into two groups. The muscle strength was measured while leg was flexed and extended at the knee joint.Research results. The research results showed that participants who received intensive physical therapy program developed better muscle strength than in standard physical therapy group. Participant’s leg muscles recovered faster in intensive physical therapy group than in standard physical therapy group.Discussion and conclusions. The participants who received physical therapy before surgery, electrostimulation and intensive physical therapy program after surgery, achieved higher levels of knee extensor and flexor muscle strength after anterior cruciate ligament reconstructive surgery than those patients undergoing a traditional physical therapy program only after surgery.Keywords: anterior cruciate ligament, intensive physical therapy, muscle strength.